Democratic Republic of Congo Sports and Culture for Development - World Bank Group (World Bank, Washington, DC, 2019)
The Democratic Republic of Congo (DRC) is a fragile, post-conflict country with high demographic growth and poor governance, all of which have devastated institutions, the economy and the social fabric. The DRC was devastated by war in the 1990s and early 2000s, which claimed millions of lives and all but destroyed much of the physical and social infrastructure of the country. In particular, DRC remains marked by high vulnerability of various populations as a consequence of past and current local and regional instability, especially in the East. A growing number of studies show that exposure to violence especially negatively affects the well-being of children and hampers their development. This report is organized as follows. Section 1 presents the DRC’s social and political context, as well as the rationale for exploring innovative approaches to build resilience and social cohesion. Section 2 summarizes some of the evidence on pathways linking sports and culture to development. Section 3 presents the DRC sports and culture institutional environment, and the last section presents a few recommendations on how to further this agenda in DRC.